Pendeteksian Kecurangan Akuntansi bagi Pengusaha UMKM melalui Pendekatan Akuntansi Forensik dan Teknologi Sederhana - Lestari, Henny Setyo; Indra Saputra (PT. Cendekia Sapta Indonesia, 2025)
This training aimed to improve financial literacy and accounting fraud detection skills among Micro, Small, and Medium Enterprises (MSME) entrepreneurs in Bekasi Raya. The program was conducted by the Faculty of Economics and Business at Trisakti University in collaboration with UMKM Pena 45 Bekasi Raya, combining theoretical and practical methods. Participants were introduced to forensic accounting, fraud detection techniques, and the use of simple technology-based accounting applications. The evaluation was carried out through pre-tests and post-tests. The results indicated a significant improvement, with the average score of participants increasing from 45 to 80 after the training. Moreover, participants gained a better understanding of the importance of internal control and transparent financial reporting. These findings highlight that practice-based training can strengthen MSME capacity in preventing accounting fraud and support business sustainability.